iKool ointment - 10% eucalyptus oil, 5% peppermint oil, 5% menthol, 5% camphor - Mohamed, Farahidah; Chatterjee, Bappaditya; Ahmad, Kausar (2020)
Label displaying the brand name iKool and main ingredients i.e 10% eucalyptus oil, 5% peppermint oil, 5% menthol, 5% camphor in ointment bases, with other instruction and labeling as required by regulatory.